Impact of a single HLA-A*24:02-associated escape mutation on the detrimental effect of HLA-B*35:01 in HIV-1 control - Murakoshi, H; Koyanagi, M; Akahoshi, T; Chikata, T; Kuse, N; Gatanaga, H; Rowland-Jones, S; Oka, S; Takiguchi, M (Elsevier, 2018)
Background HLA-B*35 is an HLA allele associated with rapid progression to AIDS. However, a mechanism underlying the detrimental effect of HLA-B*35 on disease outcome remains unknown. Recent studies demonstrated that most prevalent subtype HLA-B*35:01 is a detrimental allele in HIV-1 clade B-infected individuals. We here investigated the effect of mutations within the epitopes on HLA-B*35:01-restricted CD8+ T cells having abilities to suppress HIV-1 replication. Methods We analyzed 16 HLA-B*35:01-restricted epitope-specific T cells in 63 HIV-1 clade B-infected Japanese B*35:01+ individuals and identified HLA-B*35:01-restricted CD8+ T cells having abilities to suppress HIV-1 replication. We further analyzed the effect of HLA-associated mutations on the ability of these T cells. Findings The breadth of T cell responses to 4 epitopes was inversely associated with plasma viral load (pVL). However, the accumulation of an Y135F mutation in NefYF9 out of the 4 epitopes, which is selected by HLA-A*24:02-restricted T cells, affected the ability of YF9-specific T cells to suppress HIV-1 replication. HLA-B*35:01+ individuals harboring this mutation had much higher pVL than those without it. YF9-specific T cells failed to suppress replication of the Y135F mutant in vitro. These results indicate that this mutation impairs suppression of HIV-1 replication by YF9-specific T cells. Interpretation These findings indicate that the Y135F mutation is a key factor underlying the detrimental effect of HLA-B*35:01 on disease outcomes in HIV-1 clade B-infected individuals.